2017
DOI: 10.1261/rna.064550.117
|View full text |Cite
|
Sign up to set email alerts
|

miR-222 isoforms are differentially regulated by type-I interferon

Abstract: Endogenous microRNAs (miRNAs) often exist as multiple isoforms (known as "isomiRs") with predominant variation around their 3'-end. Increasing evidence suggests that different isomiRs of the same family can have diverse functional roles, as recently demonstrated with the example of miR-222-3p 3'-end variants. While isomiR levels from a same miRNA family can vary between tissues and cell types, change of templated isomiR stoichiometry to stimulation has not been reported to date. Relying on small RNA-sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 29 publications
9
60
0
Order By: Relevance
“…Moreover, microRNA isomiRs might not target the same proteins and, thus, depending on the sequence of the microRNAs found in milk, such approaches could mislead investigators on the real targets of milk microRNAs (Cloonan et al., ; Neilsen, Goodall, & Bracken, ; Nejad et al., ; Ple et al., ; Tan et al., ; Yu et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Moreover, microRNA isomiRs might not target the same proteins and, thus, depending on the sequence of the microRNAs found in milk, such approaches could mislead investigators on the real targets of milk microRNAs (Cloonan et al., ; Neilsen, Goodall, & Bracken, ; Nejad et al., ; Ple et al., ; Tan et al., ; Yu et al., ).…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…Recently, it has been shown that the use of assays designed for the analysis of canonical miRNAs can lead to problems due to the finding that isomiRs are quite common and their levels are affected in biological models and diseases [42,45]. In this context, the polyadenylation-based methods are less affected by changes in isomiRs [45,46].…”
Section: Isomirs and Analysis Of Expression By Qpcr-based Methodsmentioning
confidence: 99%
“…46,50 Furthermore, extensive changes in isomiRs have been observed upon stimulation, including for key immune miRNAs. 51 For instance, upon stimulation by interferon, mir-222 expresses shorter isoforms, which are associated to lower apoptosis, 52,53 highlighting how changes of miRNA isoform can contribute to regulate the response to immune stimuli.…”
Section: Impact Of Mirna-mediated Degradation On Immune Responsementioning
confidence: 99%